Adopting an Integrated Behavioral Model Approach to the Study of News Media Exposure: A Focus on Experiential and Instrumental Attitudes Toward Politics. Issue 4 (4th July 2017) - Holbert, R. Lance; Zeng, Chen; Robinson, Nicholas W.
Abstract : Stepping beyond traditional mass communication and political communication frameworks, this study utilizes the integrated behavioral model to predict traditional broadcast and print news media exposure. Specific focus is given to experiential (Is politics interesting?) and instrumental (Is politics important?) attitudes. A secondary analysis is performed on 2010–2014 World Values Survey data ( N = 6, 961) consisting of representative samples collected from the United States, Germany, Australia, and Sweden. Interest is a statistically significant predictor of both types of news media exposure, but importance and Interest × Importance are statistically significant for broadcast only. The positive predictive value of political interest for broadcast is isolated to only those individuals who perceive politics to be of low personal importance. Discussion focuses on task difficulty when comparing broadcast and print news media exposure and the theoretical implications of the study's findings. In addition, a research agenda based on the integrated behavioral model is proposed for the study of news media engagement.